Dimethyl(4-methylphenyl)ammonium naphthalene-1,5-disulfonate dihydrate - Wei, Bin (International Union of Crystallography, 2011)
The asymmetric unit of the organic–inorganic hybrid salt, 2C(9)H(14)N(+)·C(10)H(6)O(6)S(2) (2−)·2H(2)O, consists of one dimethyl(4-methylphenyl)ammonium cation, one half of a naphthalene-1,5-disulfonate anion lying on a crystallographic centre of inversion, and one water molecule. In the crystal, O—H⋯O(S) and N—H⋯OH(2) hydrogen bonds link the cations and anions forming ring motifs.